Dihydroartemisinin mediating PKM2-caspase-8/3-GSDME axis for pyroptosis in esophageal squamous cell carcinoma. (1st December 2021) - Jiang, Mingxia; Wu, Yiming; Qi, Ling; Li, Lisha; Song, Dongfeng; Gan, Junqing; Li, Yanjing; Ling, Xiaodong; Song, Chengxin
Abstract: Pyroptosis is a novel type of pro-inflammatory programmed cell death that has been strongly reported to be related to inflammation, immune, and cancer. Dihydroartemisinin (DHA) has good anti-tumor properties. However, the exact mechanism by which DHA induces pyroptosis to inhibit esophageal squamous cell carcinoma (ESCC) remains unclear. After applying DHA treatment to ESCC, we found that some dying cells exhibited the characteristic morphology of pyroptosis, such as blowing large bubbles from the cell membrane, accompanied by downregulation of pyruvate kinase isoform M2 (PKM2), activation of caspase-8/3, and production of GSDME-NT. Meanwhile, it was accompanied by an increased release of LDH and inflammatory factors (IL-18 and IL-1β). Both knockdown of GSDME and application of caspase-8/3 specific inhibitors (z-ITED-FMK/Ac-DEVD-CHO) significantly inhibited DHA-induced pyroptosis. However, the former did not affect the activation of caspase-3. In contrast, overexpression of PKM2 inhibited caspase-8/3 activation as well as GSDME-N production. Furthermore, both si-GSDME and OE-PKM2 inhibited DHA-induced pyroptosis in vivo and in vitro. Therefore, the results suggest that DHA can induce pyroptosis of ESCC cells via the PKM2-caspase-8/3-GSDME pathway. Implication: In this study, we identified new mechanism of DHA in inhibiting ESCC development and progression, and provide a potential therapeutic agent for the treatment of ESCC.